Inbreeding and genetic load in a pair of sibling grouse species: Tetrastes sewersowi and T. bonasia - Kai Song; Tom van der Valk; Bin Gao; Peter Halvarsson; Yun Fang; Wendong Xie; Siegfried Klaus; Zhiming Han; Yue-Hua Sun; Jacob Höglund (Avian Research)
Genetic load and inbreeding are recognized as important factors to be considered in conservation programs. Elevated levels of both can increase the risk of population extinction by negatively impacting fitness-related characters in many species of plants and animals, including humans (inbreeding depression). Genomic techniques are increasingly used in measuring and understanding genetic load and inbreeding and their importance in evolution and conservation. We used whole genome resequencing data from two sibling grouse species in subarctic Eurasia to quantify both. We found a large range of inbreeding measured as FROH (fraction of runs of homozygosity) in individuals from different populations of Chinese Grouse (Tetrastes sewerzowi) and Hazel Grouse (T. bonasia). FROH estimated from genome-wide runs of homozygosity (ROH) ranged from 0.02 to 0.24 among Chinese Grouse populations and from 0.01 to 0.44 in Hazel Grouse. Individuals from a population of Chinese Grouse residing in the Qilian mountains and from the European populations of Hazel Grouse (including samples from Sweden, Germany and Northeast Poland) were the most inbred (FROH ranged from 0.10 to 0.23 and 0.11 to 0.44, respectively). These levels are comparable to other highly inbred populations of birds. Hazel Grouse from northern China and Chinese Grouse residing in the Qinghai-Tibetan Plateau showed relatively lower inbreeding levels. Comparisons of the ratio between deleterious missense mutations and synonymous mutations revealed higher levels in Chinese Grouse as compared to Hazel Grouse. These results are possibly explained by higher fixation rates, mutational melt down, in the range-restricted Chinese Grouse compared to the wide-ranging Hazel Grouse. However, when we compared the relatively more severe class of loss-of-function mutations, Hazel Grouse had slightly higher levels than Chinese Grouse, a result which may indicate that purifying selection (purging) has been more efficient in Chinese Grouse on this class of mutations.